Zakres kontroli Naczelnego Sądu Administracyjnego (w świetle orzecznictwa sądowego) - Świątkiewicz, Jerzy (Wydział Prawa i Administracji UAM, 1984)
Three years have passed on September 1st since judicial review of administrative decisions was returned in Poland as principle of the system. This function is performed by a special court which is the Supreme Administrative Court (SAC). Simultaneously, specific provisions were upheld, by virtue of which review of administrative decisions could be sporadically performed by common courts of law and by district courts of labor and social security, According to the Constitutional principle positioning the Supreme Court as the highest judicial organ supervising judicial decisions of a l l courts, it can: overrule decisions of the Supreme Administrative Court by means of extraordinary appeal against a valid judgement answer legal queries directed to it, as well as resolve guiding principles for the judiciary also in the range of administrative law. On describing model of the SAC competence, the Polish legislator adopted a principle of enumerating clause specifying 20 categories of most typical cases in relations of administrative organ — citizen in art. 196 § 2 of code of administrative procedure, when final decision' of administrative instances can be appealed against to court. Complaint on no decision given can be also lodged in those cases. The SAC competence is further extended in the other acts eg. in cases of censorship or taxation including. State enterprises and other State organizational units. Frequent doubts can be raised in applying the enumerating clause, as to possibility of judicial action on account of ambivalent or too general definition of categories of cases. Similar doubts appear in the notion of „administrative decision" and legal grounds of giving it. Another problem is the range of judicial review in cases where the legislator left decisiongiving or its contents to the discretion of organ, or when the so-called not precise terms are being used. Three year judicial practice indicates that the Court aims at strengthening the institution of judicial review of administrative decisions as the principle of the system. It is manifested by: — following the principle of presumed admissibility of action in case of doubt (in dubio pro actione), — interpreting the notion of "decision" in a way enabling — a wide range of control of administration and protection of rights of citizens and their organizations. A decision is not excluded from judicial review when it bears a wrong name or is lacking proper external form. On the other hand it is avoided to interfere into a sphere of internal affairs of administration and regulated by not being generally valid provisions, i.e. enacted without a statutory authorisation. Was there any duty imposed on a citizen by decision given on a grounds of these provisions, the SAC would find the decision invalid, — bringing under control all decisions of organizational units which are not organs of State administration in their nature if it is only ascertained that they realize a function of State administration, — complete review of decisions given on grounds of provisions containing not precise terms known also as non clearly defined ones and establishing their judicial interpretation, — review of decisions given at discretion of administration, the Court establishes only whether a case allowed for giving a discretionary decision, or it could be barred at discretion (in refusal). It is also stated whether the procedural regulations were followed, whether substantiation of decision is consistent with the results of proceedings to take evidence, — performing indirect control of legality of executory acts, refusal to apply any act which is inconsistent with statutory law. The Court attempted at making administration follow the principle that imposing duties upon citizens or refusal to grant them rights or refusing them right to behave according to their will can take place only when organ of administration is authorised to do so by the explicit legal provision. Opposition to give administrative decision on grounds of non statutory provisions (not originating in statutes) helps in avoiding regulating relations administrative organ — citizen on their grounds when individual cases have to be settled with by means of decision. Different opinion of the Supreme Court can be raised in some cases, two year practice of the SAC recognizing that decisions of entering and dissolving labor contracts with nominated employees belong to the category of "matters of employment" and are one of 20 categories of cases being under the cognizance of the SAC was objected by the supreme judicature. Judicial decisions related to establishing a scope of judicial control (review) rouse a vivid interest among legal scholars.
Scope of control of the Supreme Administrative Court in the light of judical decisions